1998
DOI: 10.1088/0268-1242/13/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Current status and issues in the surface passivation technology of mercury cadmium telluride infrared detectors

Abstract: Surface passivation has been recognized as a crucial step in the fabrication of mercury cadmium telluride photoconductive as well as photovoltaic detectors. The subject has attracted considerable attention in the past and several reviews existed by 1991. The subject matter, however, received added impetus with the development of techniques like MOCVD and MBE and recently there has been considerable work on MCT passivation using in situ grown II-VI semiconductors. In this report, we have tried to give the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…9 Charge accumulation is particularly strong on the surface of InAs ͑Ref. 10͒ and Hg 1−x Cd x Te, 11 but as pointed out in our previous publication on InAs, 9 the very short spin lifetime in this region is likely to be detrimental in lateral devices where current flows along the surface. Consequently, we have explored the spin relaxation properties of InSb films of various thicknesses to determine the optimum structure for spintronic applications.…”
Section: Introductionmentioning
confidence: 87%
“…9 Charge accumulation is particularly strong on the surface of InAs ͑Ref. 10͒ and Hg 1−x Cd x Te, 11 but as pointed out in our previous publication on InAs, 9 the very short spin lifetime in this region is likely to be detrimental in lateral devices where current flows along the surface. Consequently, we have explored the spin relaxation properties of InSb films of various thicknesses to determine the optimum structure for spintronic applications.…”
Section: Introductionmentioning
confidence: 87%
“…Creation of such layers can improve the thre− shold characteristics of infrared detectors based on HgCdTe by reducing the influence of the surface recombination on the lifetime of photocarriers in the volume of the epitaxial film [5]. Characteristics of detectors based on HgCdTe lar− gely depend on the parameters of the insulator passivation coatings and their interfaces with the semiconductor [7,8], as well as on the mechanisms of generation of charge car− riers in the space charge region [4]. Therefore, investigation of the characteristics of metal−insulator−semiconductor structures (MIS structures) based on heteroepitaxial MBE HgCdTe remains an actual task.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is necessary to passivate the surface of CMT in order to reduce these surface currents as well as to maintain electrical and chemical stability. The physical and chemical properties of CdTe are very suitable for use as passivation materials for CMT [1,2]. Considering the various characteristics such as bandgap, crystal struc− ture, chemical binding, phase diagram, electrical properties, adhesion, growth methods and infrared transmission it is concluded that CdTe have emerged as strong candidate for passivation of CMT devices.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the various characteristics such as bandgap, crystal struc− ture, chemical binding, phase diagram, electrical properties, adhesion, growth methods and infrared transmission it is concluded that CdTe have emerged as strong candidate for passivation of CMT devices. Recently, in situ epitaxially grown CdTe has been used as a passivation layer in order to minimize the problems associated with lattice mismatch and surface contamination generally associated with the depo− sited passivants [1]. If the CdTe layer is grown in situ after the growth of the CMT IR absorber, no contamination is likely to occur at the CdTe/HgCdTe interface.…”
Section: Introductionmentioning
confidence: 99%